Could “digital gold” resist global supply chain pressure? - Qin, Men; Su, Chi-Wei; Wang, Yunxu; Doran, Nicoleta Mihaela (Technological and Economic Development of Economy, 2024)
Exploring the safe-haven characteristics of bitcoin from novel perspectives is crucial to diversify the investment and reap the benefits. This investigation employs bootstrap full-and sub-sample techniques to probe time-varying interrelation between global supply chain pressure (GSCP) and bitcoin price (BP), and further answer if “digital gold” could resist the strains of global supply chain. The empirical outcomes suggest that GSCP positively and negatively affects BP. The positive influence points out that high GSCP might boost the international bitcoin market, driving BP to rise, which indicates that “digital gold” could resist the pressures of global supply chain. But the negative effect of GSCP on BP could not support the above view, mainly affected by the weak purchasing power and more valuable assets, which is not consistent with the assumption of the inter-temporal capital asset pricing model (ICAPM). In turn, GSCP is adversely affected by BP, highlighting that the international bitcoin market may be viewed as a stress reliever for the global supply chain. Against a backdrop of the deteriorative Russia-Ukraine war and the intensifying global supply chain crisis, the above conclusions could bring significative lessons to the public, enterprises and related economies.First published online 17 April 2023